2016
DOI: 10.1186/s12933-016-0356-y
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of dapagliflozin in patients with type 2 diabetes and different risk categories: a meta-analysis

Abstract: BackgroundA pre-specified meta-analysis of cardiovascular (CV) events from 21 phase 2b/3 dapagliflozin clinical trials was undertaken to characterise the CV profile of dapagliflozin. This showed no increase in CV risk with dapagliflozin compared with control (placebo or comparator treatment) with or without background glucose-lowering therapies. The analysis reported here aimed to characterise the CV profile of dapagliflozin in subgroups of patients in these 21 studies grouped by degree of CV risk, based on bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0
17

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(117 citation statements)
references
References 60 publications
5
95
0
17
Order By: Relevance
“…Furthermore, use of dapagliflozin seemed to have a neutral effect on the risk for stroke (HR 0.999; 95% CI 0.536 to 1.864) 31. However, meta-analytic data of CV events from phase II and III trials of canagliflozin were reported in the European Medicines Agency assessment report, and among other CV outcomes examined, a slight trend for a higher stroke risk was noted among patients on canagliflozin treatment (HR1.47; 95% CI 0.83 to 2.59).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, use of dapagliflozin seemed to have a neutral effect on the risk for stroke (HR 0.999; 95% CI 0.536 to 1.864) 31. However, meta-analytic data of CV events from phase II and III trials of canagliflozin were reported in the European Medicines Agency assessment report, and among other CV outcomes examined, a slight trend for a higher stroke risk was noted among patients on canagliflozin treatment (HR1.47; 95% CI 0.83 to 2.59).…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effect of dapagliflozin on cardiovascular risk reduction has also been demonstrated in another meta-analysis by Sonesson et al [23]. The incidence of MACE and unstable IHD in the dapagliflozintreated group in relations to control group matched for age, BMI, duration of diabetes, smoking, eGFR, LDL cholesterol and blood pressure were analysed.…”
Section: Dapagliflozin Therapy and Cardiovascular Complicationsmentioning
confidence: 72%
“…The incidence of MACE and unstable IHD in the dapagliflozintreated group in relations to control group matched for age, BMI, duration of diabetes, smoking, eGFR, LDL cholesterol and blood pressure were analysed. After about four years of treatment, dapagliflozin has been shown to reduce the risk of MACE and/or unstable angina in all groups of patients, even in those with a history of cardiovascular events and hypertension [23].…”
Section: Dapagliflozin Therapy and Cardiovascular Complicationsmentioning
confidence: 99%
“…Due to its rapid effects on kidney, dapagliflozin rapidly reduces also glucose toxicity. Several registrative trials confirmed that the insulin-independent fast glucose-lowering effect of dapagliflozin does not generate specific metabolic or apparent CV harm [8]. A possible direct effect on the alpha cell leading to increase glucagon secretion has been claimed [9].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…A simulated projection by using the Archimedes model showed that adding dapagliflozin to other antidiabetic agents further decreases CV and microvascular complications associated with T2DM over a 20-year period [62]. Thus, dapagliflozin has the potential for a beneficial effect both in the overall population and in those with a history of CV disease [8].…”
Section: Dapagliflozin and CV Riskmentioning
confidence: 99%